Energy renovation of an existing building in Nicosia Cyprus and investigation of the passive contribution of a BIPV/T double façade system: A case-study - Constantina Theokli (Elsevier, 2021)
The European regulatory shift towards energy-efficient buildings and nearly zero energy buildings (NZEB) leads architects and engineers to the need for investigation of new innovative design methodologies. The reduction of the energy demand for cooling, heating and artificial lighting is now mandatory for new buildings and for large renovations of existing buildings, in order to comply with these new regulations. This is a challenge since the majority of the current building stock is consisted by over than 25-year-old existing buildings, which are inefficient in terms of energy needs. The aim of this study is to completely renovate an existing building in the centre of Nicosia, Cyprus, by applying a novel double façade system. This is consisted by a combination of a novel Building Integrated Photovoltaic/Thermal system (BIPV/T) and a Corridor Type Double façade system, which acts autonomously in every floor. The proposed research starts with an analysis of building and site geometry and moves through a literature review, along with the presentation of case studies where active solar energy systems are integrated on double building facades. Digital energy simulations are performed where the proposed double façade’s passive contribution is investigated. At the same time, these simulations aim to analyse whether the system can cover the energy needs of the aforementioned building. The investigation focuses into calculating the façade’s electricity production potential, whilst its passive contribution is recorded through the reduction potential of the building’s energy needs for heating, cooling and artificial lighting. Through a 3D simulations modelling, the existing energy needs are recorded and then compared to the calculated needs of the renovated building. The ultimate aim of this research is to determine whether the use of BIPV/T double façade solutions for the refurbishment of existing buildings consist an environmental viable solution.